Tourism and the sustainable development goals in Southeast Asia - Trupp, Alexander *; Dolezal, Claudia (Society for South-East Asian Studies, 2020)
The Sustainable Development Goals (SDGs), a set of 17 goals adopted in 2015, are aimed at reconciling economic, social, and ecological progress at a global level – ensuring a sustainable future for developed and developing countries alike. Tourism in Southeast Asia is particularly thought to make an important contribution – given its substantial economic role – to the SDGs. While the United Nations initially only linked three SDGs to tourism, it bears often underused potential to contribute to the entire set of goals. Yet, the relationship between tourism and sustainable development is regarded as ambiguous – an industry strongly characterized by an overdependence on international tourists and foreign investment, showing a patchy track record of negative impacts and conflicts. In addition, in times of COVID-19, tourism has become a dormant industry, leaving behind substantial economic gaps, particularly in Southeast Asia. With regards to the SDGs, little research exists to date that investigates whether and how tourism can contribute to reaching the goals’ targets to achieve a more sustainable development. This article thus outlines the current situation for tourism for development in Southeast Asia, and discusses the links between tourism and the SDGs, particularly at a time when the region – and theindustry at large – have been strongly impacted.